Exploring the Digital Discourse: Representations and Perceptions of Islam Nusantara in Online Resources - Huda, Sokhi; Bustami, Mohammad Reevany; Ansori , Moh.; Bustomi, Abu Amar; Maksum, Imam; Jamil, Amidatus Sholihat; Armiah, Armiah; Fatihia, Wifda Muna (Bukhori: Kajian Ekonomi dan Keuangan Islam, 2025)
Purpose: This study investigates how Islam Nusantara is represented, contested, and legitimized across digital platforms, focusing on its role as both a cultural-religious discourse and a site of ideological negotiation. Methodology/approach: A mixed-method triangulation was employed, combining quantitative content analysis, qualitative framing analysis, and philological examination of digitized manuscripts. Validity and reliability were maintained through systematic coding, intercoder agreement, peer debriefing, re-coding cycles, and cross-referencing of manuscript variants. Results/findings: The quantitative findings reveal that Islam Nusantara discourse appeared in 2,354 posts across three major platforms, with 62% inclusivist frames, 28% nationalist frames, and 10% critical frames. Frequently recurring terms such as religious moderation, Islam rahmatan lil-‘alamin, and local culture confirm its online resonance. Framing analysis uncovers inclusivist, nationalist, and critical lenses shaping the discourse, while philological analysis demonstrates continuity with historical traditions of Islam–local culture synthesis. Conclusions: Islam Nusantara’s digital representation is multi-dimensional, shaped by both contemporary ideological contestation and deep-rooted textual legitimacy. The integration of quantitative, qualitative, and philological evidence provides a comprehensive framework for understanding religious discourse in the digital age. Limitations: The data are time-bound (up to June 2023) and limited to selected digital platforms, which may not fully capture the broader scope of Islam Nusantara debates. Contribution: The study theoretically introduces a triangulated methodological model (content, framing, philological) in digital religion research. Practically, it highlights Islam Nusantara’s potential to strengthen moderate Islamic discourse and support digital religious policies that foster inclusivity and cultural integration.